Bilateral Paraventricular Nucleus Upregulation of Extracellular Superoxide Dismutase Decreases Blood Pressure by Regulation of the NLRP3 and Neurotransmitters in Salt-Induced Hypertensive Rats - Qing Su; Xiao-Jing Yu; Xiao-Min Wang; Hong-Bao Li; Ying Li; Juan Bai; Jie Qi; Nianping Zhang; Kai-Li Liu; Yan Zhang; Guo-Qing Zhu; Yu-Ming Kang (Frontiers Media S.A., 2021)
Aims: Long-term salt diet induces the oxidative stress in the paraventricular nucleus (PVN) and increases the blood pressure. Extracellular superoxide dismutase (Ec-SOD) is a unique antioxidant enzyme that exists in extracellular space and plays an essential role in scavenging excessive reactive oxygen species (ROS). However, the underlying mechanism of Ec-SOD in the PVN remains unclear.Methods: Sprague-Dawley rats (150-200 g) were fed either a high salt diet (8% NaCl, HS) or normal salt diet (0.9% NaCl, NS) for 6 weeks. Each group of rats was administered with bilateral PVN microinjection of AAV-Ec-SOD (Ec-SOD overexpression) or AAV-Ctrl for the next 6 weeks.Results: High salt intake not only increased mean arterial blood pressure (MAP) and the plasma noradrenaline (NE) but also elevated the NAD(P)H oxidase activity, the NAD(P)H oxidase components (NOX2 and NOX4) expression, and ROS production in the PVN. Meanwhile, the NOD-like receptor protein 3 (NLRP3)-dependent inflammatory proteins (ASC, pro-cas-1, IL-β, CXCR, CCL2) expression and the tyrosine hydroxylase (TH) expression in the PVN with high salt diet were higher, but the GSH level, Ec-SOD activity, GAD67 expression, and GABA level were lower than the NS group. Bilateral PVN microinjection of AAV-Ec-SOD decreased MAP and the plasma NE, reduced NAD(P)H oxidase activity, the NOX2 and NOX4 expression, and ROS production, attenuated NLRP3-dependent inflammatory expression and TH, but increased GSH level, Ec-SOD activity, GAD67 expression, and GABA level in the PVN compared with the high salt group.Conclusion: Excessive salt intake not only activates oxidative stress but also induces the NLRP3-depensent inflammation and breaks the balance between inhibitory and excitability neurotransmitters in the PVN. Ec-SOD, as an essential anti-oxidative enzyme, eliminates the ROS in the PVN and decreases the blood pressure, probably through inhibiting the NLRP3-dependent inflammation and improving the excitatory neurotransmitter release in the PVN in the salt-induced hypertension.